Meme Culture on TikTok: An Analysis of Ryanair’s Visual Communication and Self-Aware Humour - Santana Lledó, Mariana; Pradana Pérez, Francisco José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
TikTok has become a pivotal platform for Generation Z. This study analyses Ryanair's visual communication strategy in Spain focus on memes and humour. A mixed methodology incorporating content analysis (n=50 videos) and survey (n=282 Gen Z users), were employed to examine the brand's identity construction and its connection with its audience. The results demonstrate that the strategic deployment of humour, memes and the visual humanisation of the brand engender a robust engagement with the user, prioritising notoriety over the conventional image and fostering interaction, a pivotal aspect in the contemporary digital visual culture.